Optimasi Proporsi Campuran Carbopol 941 dan CMC-Na dalam Pembuatan Gel Lendir Bekicot (Achatina fullica Ferr.) secara Simplex Lattice Design - ELISABETH APRILIA; ILHAM KUNCAHYO; Siti Aisiyah (Fakultas Farmasi Universitas Setia Budi, 2012)
Snail (Achatina fulica Ferr) mucus efficacious as cure wounds. The use of snail mucus directly considered less practical, so that made the gel preparation. This study aims to obtain the optimum formula of snail mucus gel from carbopol 941 and CMC-Na mixtures using simplex lattice design. Snail mucus obtained by solving the top shell snail then shell reversed for inside snail mucus out. Optimum gel formula based on the simplex lattice design with 2 components, i.e: carbopol 941 (K) and CMC-Na (C) using 3 formulas, i.e: formula I (100% K: 0% C), formula II (50% K: 50% C) and formula III (0% K: 100% C). The physical properties observed were viscosity, adhesiveness and dispersive, which then is used to make the SLD equation. The equation used to make the optimum formula gel from the total response of the most large gel physical nature. Results obtained from the simplex lattice design equation compared with actual test results with t-test (T-test). The results showed an optimum gel formula of snail mucus obtained from of 30% carbopol 941 and 70% CMC-Na mixtures. From the results of t-test (T-tesf) against viscosity, adhesiveness and dispersive showed no significant difference between the predictions with actual experimental results.